A Prospective Cohort Study on Serum Glycosylated Fibronectin as a Biomarker for Early Prediction of Preeclampsia - Vibhuti Thakur; Kavyashree; Poonam Mathur (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Preeclampsia (PE) is a significant hypertensive disorder of pregnancy contributing to maternal and neonatal morbidity and mortality. Early detection and intervention are crucial to reducing the burden of this disease. Glycosylated fibronectin (GlyFn) has emerged as a potential biomarker for the early prediction of PE. Materials and Methods: A prospective cohort study was conducted in the Department of Obstetrics and Gynaecology at MGM Medical College and MTH Hospital, Indore. A total of 140 pregnant women with risk factors for PE were enrolled between December 2022 and March 2023. Serum GlyFn levels were measured using an ELISA-based method. Participants were categorized based on GlyFn levels into normal (<250 μg/mL), and positive groups (250–350 μg/mL, 350–500 μg/mL, >500 μg/mL). GlyFn levels were monitored every 4 weeks, and clinical outcomes, including PE onset, maternal complications, and fetal outcomes, were analyzed. Statistical analysis was performed using ANOVA, Pearson correlation, and Chi-square tests. Results: The majority of participants were nulliparous (33.3%), with a mean age of 24.3 years. Elevated GlyFn levels (>250 μg/mL) were significantly associated with the development of PE (P < .001). The sensitivity, specificity, positive predictive value, and negative predictive value of GlyFn at a cutoff of 250 μg/mL were 92.3, 88.9, 96, and 80%, respectively. The average gestational age (GA) at GlyFn positivity was inversely correlated with the GA at PE onset, with early detection providing a larger intervention window. Maternal complications included postpartum hemorrhage (21.44%) and thrombocytopenia (15%), while fetal complications included preterm birth (23.65%) and intrauterine growth restriction (9.3%). Conclusion: Serum GlyFn is a promising biomarker for early prediction of PE, enabling timely interventions to improve maternal and fetal outcomes. A GlyFn cutoff of 250 μg/mL showed high diagnostic accuracy. Further research is required to validate its clinical utility and integrate it into routine antenatal care.